Noncanonical Transmission of a Measles Virus Vaccine Strain from Neurons to Astrocytes - Katrien C. K. Poelaert (American Society for Microbiology, 2021)
Viruses are the most important cause of infectious encephalitis in mammals worldwide; several thousand people, primarily the very young and the elderly, are impacted annually, and few therapies are reliably successful once neuroinvasion has occurred. To understand how viruses contribute to neuropathology, and to develop tools to prevent or ameliorate such infections, it is crucial to define if and how viruses disseminate among the different cell populations within the highly complex central nervous system.